2018
DOI: 10.1007/s00259-018-3953-z
|View full text |Cite
|
Sign up to set email alerts
|

Defining the optimal method for measuring baseline metabolic tumour volume in diffuse large B cell lymphoma

Abstract: PurposeMetabolic tumour volume (MTV) is a promising prognostic indicator in diffuse large B cell lymphoma (DLBCL). Optimal thresholds to divide patients into ‘low’ versus ‘high’ MTV groups depend on clinical characteristics and the measurement method. The aim of this study was to compare in consecutive unselected patients with DLBCL, different software algorithms and published methods of MTV measurement using FDG PET.MethodPretreatment MTV was measured on 147 patients treated at Guy's and St Thomas’ Hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
119
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 44 publications
(97 reference statements)
11
119
0
1
Order By: Relevance
“…Different procedures and a wide range of threshold levels have been proposed to calculate MTV. 35,43,49 Moreover, the prognostic effect of MTV has been estimated using cut-points that are heavily cohort-dependent, being generated by ROC analysis of small series. In this study, we chose to use a segmentation method with a fixed-threshold at SUV 5 2.5 43 that, compared with the widely used percentage threshold at 41% of SUVmax, maintains a similar accuracy and offers better tumor coverage, 41 particularly in lesions with heterogeneous FDG uptake distribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different procedures and a wide range of threshold levels have been proposed to calculate MTV. 35,43,49 Moreover, the prognostic effect of MTV has been estimated using cut-points that are heavily cohort-dependent, being generated by ROC analysis of small series. In this study, we chose to use a segmentation method with a fixed-threshold at SUV 5 2.5 43 that, compared with the widely used percentage threshold at 41% of SUVmax, maintains a similar accuracy and offers better tumor coverage, 41 particularly in lesions with heterogeneous FDG uptake distribution.…”
Section: Discussionmentioning
confidence: 99%
“…35,43,49 Moreover, the prognostic effect of MTV has been estimated using cut-points that are heavily cohort-dependent, being generated by ROC analysis of small series. In this study, we chose to use a segmentation method with a fixed-threshold at SUV 5 2.5 43 that, compared with the widely used percentage threshold at 41% of SUVmax, maintains a similar accuracy and offers better tumor coverage, 41 particularly in lesions with heterogeneous FDG uptake distribution. 49 Although the lack of standardization endangers the reproducibility of the results obtained in retrospective studies, there is increasing evidence of the prognostic value of quantitative parameters obtained from 18FDG-PET/CT in patients with different non-Hodgkin lymphoma subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total lesion glycolysis (TLG)-defined as SUVmean in a volume multiplied by the corresponding MTV-seems to perform similarly [7] or inferiorly [6,8] in predicting outcome of DLBCL patients. Various segmentation methods to measure MTV and TLG are being used in clinical lymphoma studies [10]: most use a fixed SUV threshold (e.g., SUV≥2.5 [7,9] or SUV≥4.0 [11]) or a percentage of SUVmax (e.g., 41 % of SUVmax [6,8,12]) to define MTV. An important finding from earlier studies in DLBCL is that optimal cutoff values range widely (220-550 ml), probably because of using different methodologies, small patient cohorts, differences in patient risk factors, and therapies [13].…”
Section: Introductionmentioning
confidence: 99%
“…Segmentation methods in these studies are generally derived from phantom experiments [4,12], or correlation with pathological specimens in lung cancer [4]. Limited data are available about the differences in ease of use in the lymphoma clinical setting and interobserver reliability of these tumor segmentation methods [10]. Previous studies in DLBCL [10], T cell [14], and Hodgkin lymphoma [15] showed that different segmentation methods, despite having different cutoff values, show comparable accuracy for predicting survival.…”
Section: Introductionmentioning
confidence: 99%